Parasitoids (Hymenoptera) of Mealybug Pests (Hemiptera: Pseudococcidae) from Southern Brazil: Molecular and Morphological Characterization - Pacheco da Silva, Vitor Cezar (2021)
Parasitoids of three mealybug pests (Hemiptera: Pseudococcidae), Planococcus ficus (Signoret), Pseudococcus sociabilis Hambleton, and Pseudococcus viburni (Signoret) have been identified for the first time in Brazil. Mealybugs were collected in fruit-growing areas along southern Brazil during 2013-2016. An integrative approach, combining morphological and molecular methods, was used to identify the Brazilian parasitoids to the species level. Fifteen species were recorded, including 14 primary parasitoids belonging to Encyrtidae and Platygastridae and a single secondary parasitoid species belonging to Signiphoridae. The encyrtid parasitoids Acerophagus flavidulus (Brethes), Anagyrus calyxtoi Noyes and Zaplatycerus sp., and the signiphorid secondary parasitoid Chartocerus axillaris De Santis are reported for the first time in Brazil.